2004
DOI: 10.1021/ie034116q
|View full text |Cite
|
Sign up to set email alerts
|

Fischer−Tropsch Synthesis over Activated-Carbon-Supported Cobalt Catalysts:  Effect of Co Loading and Promoters on Catalyst Performance

Abstract: The effects of Co loading and K, Ce, and Zr promoters on initial activities and selectivities of activated-carbon-supported cobalt (Co/AC) Fischer-Tropsch synthesis (FTS) catalysts, were studied under conditions of 240 °C, 2.4 MPa, 650 h -1 , and H 2 /CO ) 2:1 in a fixed-bed reactor. The reduction and metal dispersion properties of the catalysts were investigated through temperature-programmed reduction (TPR) and CO chemisorption. Detectable hydrocarbons up to C 20 were formed on the Co/AC catalysts. Co loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 46 publications
8
60
0
Order By: Relevance
“…The site specific activity (TON) of K promotion also goes through a maximum with K content, consistent with earlier literature reports [4]. Results for K promotion of Co are more ambiguous [30]. (ii) Cr promotion effects on Fe:Co are also consistent with literature reports on Fe promotion.…”
Section: Impact Of the Promoters On The Fe:co/tio 2 Catalystssupporting
confidence: 89%
See 1 more Smart Citation
“…The site specific activity (TON) of K promotion also goes through a maximum with K content, consistent with earlier literature reports [4]. Results for K promotion of Co are more ambiguous [30]. (ii) Cr promotion effects on Fe:Co are also consistent with literature reports on Fe promotion.…”
Section: Impact Of the Promoters On The Fe:co/tio 2 Catalystssupporting
confidence: 89%
“…Reports also indicate that K promoted Co catalysts on SiO 2 inhibits Co reducibility [29] while on C [30] the role of K (ratio 15/2 Co/K; very high) is to decrease FT activity and CH 4 selectivity and increase WGS activity. Another role for K promotion on Fe appears to be to enhance graphite and metal carbide formation [31,32].…”
Section: Potassium Promotionmentioning
confidence: 99%
“…Our previous work indicated that activated carbonsupported Co catalyst favored the formation of C 10 -C 20 hydrocarbon in Fischer-Tropsch Synthesis [17]. Meantime, we have also reported that the addition of ZrO 2 into Co/AC catalyst could increase CO conversion and enhance the selectivity to C 10 -C 20 hydrocarbon [17,18].…”
Section: Introductionmentioning
confidence: 76%
“…11,12 Selection of a support with a proper interaction with the active phase (or metal precursor) is of prime importance because of the balance between the reducibility and the dispersion of the active phase that defines FTS performance. Supports such as alumina, 13,14 silica, 15,16 titania 17 and carbon materials 10,[18][19][20][21][22] have been reported by many groups. Among them, carbon materials are considered to be more inert than the conventional oxide materials.…”
Section: Introductionmentioning
confidence: 99%